A Comparative Analysis of Once-daily and Twice-daily Formulation of Tacrolimus in De Novo Kidney Transplant Recipients - Ferhatoglu, Murat Ferhat (Sisli Etfal Hastan Tip Bul, 2021)
OBJECTIVES: We aimed to compare the once-daily and twice-daily formulation of tacrolimus concerning the efficiency and effects on graft function in de novo kidney transplant patients. METHODS: Twenty once-daily (TAC-OD) and twenty twice-daily (TAC-BID) tacrolimus administrated de novo kidney recipients who had received initial immunosuppressive therapy according to protocols at our institution (0.2 mg/kg of tacrolimus combined with 1000 milligrams of steroid taper plus 720 mg of mycophenolate and with 2.5mg/kg anti-thymocyte globulin) assessed concerning demographics, drug doses and blood concentration, and graft function. RESULTS: The mean tacrolimus blood concentration measurements were higher in the TAC-OD group in the first sixty days after transplantation, and the TAC-OD group showed more blood concentration overshoots/fluctuations in the first 30 days of the treatment. The initial drug dose was significantly higher in the TAC-OD group than the TAC-BID group (p=0.04). There was no meaningful difference among groups according to graft function (creatinine measurements) (p>0.05). CONCLUSION: Between de novo kidney recipients, the new TAC-OD formulation presents a similar short-term efficacy profile as TAC-BID. However, a higher daily dosage of TAC-OD is needed to achieve similar blood concentrations in the early postoperative period.